Tsunami‐driven gravity waves in the presence of vertically varying background and tidal wind structures. Issue 10 (17th May 2017) - Laughman, B.; Fritts, D. C.; Lund, T. S.
Abstract: Many characteristics of tsunami‐driven gravity waves (TDGWs) enable them to easily propagate into the thermosphere and ionosphere with appreciable amplitudes capable of producing detectable perturbations in electron densities and total electron content. The impact of vertically varying background and tidal wind structures on TDGW propagation is investigated with a series of idealized background wind profiles to assess the relative importance of wave reflection, critical‐level approach, and dissipation. These numerical simulations employ a 2‐D nonlinear anelastic finite‐volume neutral atmosphere model which accounts for effects accompanying vertical gravity wave (GW) propagation such as amplitude growth with altitude. The GWs are excited by an idealized tsunami forcing with a 50 cm sea surface displacement, a 400 km horizontal wavelength, and a phase speed of 200 ms −1 consistent with previous studies of the tsunami generated by the 26 December 2004 Sumatra earthquake. Results indicate that rather than partial reflection and trapping, the dominant process governing TDGW propagation to thermospheric altitudes is refraction to larger and smaller vertical scales, resulting in respectively larger and smaller vertical group velocities and respectively reduced and increased viscous dissipation. Under all considered background wind profiles, TDGWs were able to attain ionospheric altitudes with appreciable amplitudes. Finally, evidence of nonlinear effects is observed and the conditions leading to their formation is discussed. Key Points: Tsunami‐driven gravity waves can attain ionospheric altitudes with appreciable amplitudes under a variety of tidal filtering environments